Has preventive medicine entered the realm of the interventional cardiologist? - Doubell, Anton (SA Heart Journal, 2017)
The result of the Preventive Angioplasty in Acute Myocardial Infarction (PRAMI) trial(1) released at the recent ESC meeting held in Amsterdam has attracted enormous interest and rightly so: if the conclusions drawn by the researchers prove correct, the management of patients presenting with a ST segment elevation myocardial infarction (STEMI) is about to undergo a major change. The authors provide evidence to support “preventive PCI” in non-infarct related coronary arteries in patients with multivessel disease undergoing angiography with the objective of opening the infarct related coronary artery. These findings challenge the long-held view, reflected in international guidelines, that PCI in this setting should be aimed only at the so-called culprit lesion. It also challenges the view that the likelihood of atheromatous plaque rupture is primarily related to the properties of the plaque (degree of inflammation, cap thickness, cholesterol content) and not the degree of stenosis.